Stable Resistance to Potato Virus Y and Potato Leafroll Virus in Transgenic Potato Plants cv. Kennebec Expressing Viral Genes Under Greenhouse and Field Conditions - Barrios Baron, Maria Pilar (2026)
Potato virus Y (PVY) and potato leafroll virus (PLRV) are the most damaging viruses for potato production worldwide. Mixed infections not only result in additive detrimental effects on plant growth and tuber yield but also complicate the development of durable and broad-spectrum viral resistance. Heterologous protection against PVY can be achieved through the expression of the coat protein (CP) of lettuce mosaic virus (LMV) (CPLMV), conferring resistance via a capsid protein-mediated mechanism. On the other hand, we have previously demonstrated that transgenic lines expressing the PLRV ORF2 (RepPLRV) exhibit resistance to different PLRV isolates. In this study, potato transgenic lines of cv. Kennebec expressing CPLMV and RepPLRV were developed to confer dual virus resistance. Transgenic and non-transgenic control plants were molecularly and phenotypically characterized in greenhouse and field conditions. Across multiple growing seasons, two selected transgenic lines consistently displayed robust resistance to both major viruses, without exhibiting yield penalties or noticeable phenotypic alterations. These results constitute a significant advancement, demonstrating that dual resistance to PVY and PLRV can be achieved while preserving the original agronomic performance of the cultivar. This breakthrough not only contributes to long-term crop productivity but also provides a more sustainable strategy for managing viral diseases in potato production.